Germline De Novo Mutation Clusters Arise During Oocyte Aging in Genomic Regions With High Double-Strand-Break Incidence. Issue 9 (September 2018) - Goldmann, Jakob M.; Seplyarskiy, Vladimir B.; Wong, Wendy S. W.; Vilboux, Thierry; Neerincx, Pieter B.; Bodian, Dale L.; Solomon, Benjamin D.; Veltman, Joris A.; Deeken, John F.; Gilissen, Christian; Niederhuber, John E.
Abstract : (Abstracted from Nat Genet 2018;50:487–492) Germline de novo mutations (DNMs) arise spontaneously in parental gametes and are both drivers of evolution and a common cause of sporadic disorders. The total number of DNMs is highly correlated with paternal age and with maternal age to a lesser extent.